New 3D method to estimate the cycling frontal area during pedalling - Ferrrer-Roca, V.; Vretos, N.; Chatzifolis, A.; Alvarez, D. (ISBS Proceedings Archive (Michigan), 2017)
Aerodynamic drag represents a high percentage of the resistive forces in cycling. The frontal area has been traditionally measured through 2D digitalization, which requires a capture and an analysis processes. In the present study, the 2D method has been compared with a new real time 3D method to measure the frontal area in three different cycling positions. High reliability (ICC>0.9) was found on both measurement methods. However there were differences between methods at the most aerodynamic positions. These differences might appear due to the capacity of the new method to measure the depth dimension, which supposes an improvement on the frontal area analysis. Furthermore, the new 3D method allows feedback of the frontal area in real time.